Search for narrow resonances in dilepton mass spectra in $pp$ collisions at $\sqrt{s}=7$ TeV - CMS collaboration (2215 authors) (2013)
A search for narrow, high-mass resonances decaying to electron or muon pairs has been performed using pp collision data collected at sqrt(s) = 7 TeV by the CMS experiment in 2011. The data sample corresponds to an integrated luminosity of approximately 5 inverse femtobarns. The event yields observed in the signal regions are consistent with predictions of the standard model backgrounds, and upper limits on the cross section times branching fraction for a resonance decaying to dileptons are extracted from a shape analysis of the dilepton invariant mass distribution. The resulting mass limits at 95% confidence level are 2330 GeV for the Z' in the Sequential Standard Model, 2000 GeV for the superstring-inspired Z'(psi) resonance, 890 (540) GeV for the Stueckelberg extension Z'(St) with the mass parameter epsilon = 0.06 (0.04), and 2140 (1810) GeV for Kaluza--Klein gravitons with the coupling parameter k/Mbar(Pl) of 0.10 (0.05). These limits are the most stringent to date.